向印尼汉语学习者的中国酒文化教学: 跨文化教学策略 - Markali, Alpin Gadman; Kurniawan, Budi; Halim, Steffi Thanissa (Confucius Institute Universitas Sebelas Maret, 2024)
This paper explores cross-cultural teaching strategies for teaching Chinese wine culture to Indonesian Chinese language learners. It begins by providing necessary background information by summarizes the historical origins and rich meanings of Chinese wine culture, as well as its differences from Indonesian wine culture. Subsequently, the paper proposes various cross-cultural teaching strategies, including using authentic materials and situational teaching, combining language teaching with cultural teaching, promoting cross-cultural understanding and communication, and enhancing learners' cultural sensitivity. These strategies aim to help students better understand and appreciate Chinese wine culture and promote cultural exchange and understanding between China and Indonesia. Finally, the paper emphasizes the importance of cross-cultural teaching strategies in teaching Chinese wine culture to Indonesian Chinese language learners and proposes some directions for future research, such as exploring more deeply the relationship between drinking habits and cultural concepts under different cultural backgrounds, and developing more targeted teaching resources and course designs. These explorations will help further improve the effectiveness of cross-cultural teaching and promote cultural exchange and cooperation between China and Indonesia.